2020
DOI: 10.1101/2020.09.09.290015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanobody-mediated control of gene expression and epigenetic memory

Abstract: Targeting chromatin regulators to specific genomic locations for gene control is emerging as a powerful method in basic research and synthetic biology. However, many chromatin regulators are large, making them difficult to deliver and combine in mammalian cells. Here, we developed a new strategy for gene control using small nanobodies that bind and recruit endogenous chromatin regulators to a gene. We show that an antiGFP nanobody can be used to simultaneously visualize GFP-tagged chromatin regulators and cont… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Recent work has demonstrated that it is possible for epigenome editing to write a stable transcriptional program that is remembered and propagated by human cells without constitutive expression of the programmable epigenetic modulators (Amabile et al, 2016;Bintu et al, 2016;Park et al, 2019;Van et al, 2021). In particular, Amabile et al (2016) showed that it was possible to heritably silence human genes by recruitment of a cocktail of DNA methyltransferase and KRAB domains.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has demonstrated that it is possible for epigenome editing to write a stable transcriptional program that is remembered and propagated by human cells without constitutive expression of the programmable epigenetic modulators (Amabile et al, 2016;Bintu et al, 2016;Park et al, 2019;Van et al, 2021). In particular, Amabile et al (2016) showed that it was possible to heritably silence human genes by recruitment of a cocktail of DNA methyltransferase and KRAB domains.…”
Section: Introductionmentioning
confidence: 99%
“…Reagents that can differentiate between the two most closely-related Tribbles proteins will be key to fully understanding the different functions of TRIB1 and TRIB2, and eventually to their targetability in disease. While nanobodies seem unlikely to be therapeutically viable option for Tribbles proteins, which are intracellular and expressed during differentiation—they could be extremely valuable as research reagents (Cheloha et al, 2020; Van et al, 2021). The three nanobodies we report here exhibit specificity for TRIB2 over both TRIB1 and TRIB3, and also differ in solution behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Although small-molecule modifiers of epigenetic silencing have been used successfully in vitro, it is likely that these would affect the developmental potential of stem cells also thereby altering efforts to mimic developmental transitions if applied to embryo models. Another possibility for controlling epigenetic silencing could lie in synthetic factors that could insulate or control the epigenetic status of user-defined genetic loci (Bintu et al, 2016;Park et al, 2016Park et al, , 2019Van et al, 2021). In the future, complex synthetic circuits could contain sensors for epigenetic silencing that trigger synthetic reversion of silencing itself.…”
Section: Perspectivementioning
confidence: 99%